STUDIES ON WATER QUAliTY AND FISH DIVERSITY OF SADATPUR LAKE IN AHMEDNAGAR DISTRICT MAHARASHTRA - Pawar, B. A. (Journal of Indian Fisheries Association, 2009)
The present study deals with the water quality and ichthyofauna of Sadatpur lake.Monthly changes in water quality parameters such as temperature, pH, dissolved oxygen (DO),total alkalinity, chlorides, sulphate, phosphate and nitrite have been studied for a period of one year beginning from January 2005 and were investigated to assess the suitability of this lake for fish and fisheries practices. All the physico-chemical parameters determined, revealed that the fluctuations in water temperature, pH, dissolved oxygen, alkalinity and nitrite, were with in the desirable limits. On the other hand, chloride and sulphate were lower where as phosphate was higher than the desirable limits. Altogether 24 fish species belonging to 17 genera and 2 orders were found to be present in the lake. Among fish species family Cyprinidae dominated the lake.The lake subsistence fishery served the need of local fishermen community.Key Words: Sadatpur lake, Water quality, Fish diversity.